USEFULNESS OF NEUTROPHILS TO LYMPHOCYTES RATIO FOR PREDICTING TROPONIN-I ELEVATION IN PATIENTS PRESENTING WITH SUSPECTED NSTE-ACUTE CORONARY SYNDROME - Awan, Muhammad Saleem; Daud, Muhammad Yousuf; Khan, Matiullah; Jehangiri, Atique-ur Rehman; -, Adnan; Jalil, Shaista (Journal of Ayub Medical College Abbottabad, 2019)
Background: Most of the admissions to the coronary care unit are patients who are having Non-ST-segment elevation acute coronary syndrome (NSTE-ACS). Inflammation has an important role in the pathogenesis of the acute coronary syndrome. Inflammatory marker such as Leukocyte counts & most importantly Neutrophils to Lymphocyte Ratio (NLR) has been found an important predictor of cardiovascular events. Few studies show the diagnostic role of Neutrophils to Lymphocyte ratio in the patient presenting with NSTE-ACS. The objective of this study was to determine the diagnostic role of Neutrophils to Lymphocytes ratio to predict the elevation of Troponin-I in patients presenting with suspected NSTE-acute coronary syndrome. Methods: This was a Descriptive Case Series study, conducted in Cardiology department Ayub Teaching Hospital/Ayub Medical College Abbottabad, from 15th May 2017 to30th December 2018. A total of 203 patients with suspected NSTE-ACS were inducted in the study by non-probability, consecutive sampling. Results: Results of this study shown a strong correlation between Neutrophils to Lymphocyte ratio (NLR) & rise in Troponin-I levels. Furthermore, results shown that at 4th quartile of Neutrophils to Lymphocyte ratio (NLR) there is high Specificity (97.8%) and very high positive predictive of value 96.7% for predicting the rise in Troponin-I levels. Conclusion: We concluded that there is a strong correlation between rising Neutrophils to Lymphocyte ratio (NLR) and cardiac Troponin-I elevation in patients presenting with suspected NSTE-acute coronary syndrome. Therefore, this parameter can be used to predict the rise in troponin level in patients presenting with suspected NSTE-ACS. Keywords: Non-ST segment elevation myocardial infarction (NSTEMI); ST-segment depression; Neutrophils to Lymphocytes ratio; Non-ST elevation acute coronary syndrome; Electrocardiogram